Peran Peraturan Desa Nomor 07 Tahun 2021 Tentang Pendirian Badan Usaha Milik Desa (BUMDes) Sejahtera Barokah Banjarsari Terhadap Potensi Wisata Taman Banjarsari Agro Community (BAC) Di Desa Banjarsari - Dyah Rakhmawati Tri Atmayanti; Machwal Huda; Hudallah Hudallah (Pusat Riset dan Inovasi Nasional, 2023)
Prioritization of the use of BUM Desa is managed on the basis of democratic village governance in accordance with the Regulations of the Minister of Villages, Development of Backward Regions, and Transmigration of the Republic of Indonesia. Prioritization of the use of Village BUM will be carried out openly, participatory, and provide benefits to the village community, on condition that the village head, the Village Consultative Agency (BPD), and all villagers succeed in presenting democratic governance. The priority of using BUM Desa is to finance the implementation of programs and activities in the field of village development and empowerment of village communities. The priority of using the Village BUM is publicized to the community by the village government in public spaces or spaces that are easily accessible to the village community. This study aims to understand and describe the influence of Banjarsari Village Bum Perdes No. 7 of 2021 on the Tourism Potential of Banjarsari Agro Community Park (BAC) in Banjarsari Village, Bandarkedungmulyo District, Jombang Regency. The research method used is Qualitative Descriptive, using the Informant in this study is the administrator of Bum Desa Banjarsari